Efficacy of adjuvant weight loss medication after bariatric surgery - Nor Hanipah, Zubaidah; Nasr, Elie C.; Bucak, Emre; Schauer, Philip R.; Aminian, Ali; Brethauer, Stacy A.; Cetin, Derrick (Elsevier, 2018)
Background: Some patients do not achieve optimal weight loss or regain weight after bariatric surgery. In this study, we aimed to determine the effectiveness of adjuvant weight loss medications after surgery for this group of patients. Setting: An academic medical center. Methods: Weight changes of patients who received weight loss medications after bariatric surgery from 2012 to 2015 at a single center were studied. Results: Weight loss medications prescribed for 209 patients were phentermine (n = 156, 74.6%), phentermine/topiramate extended release (n = 25, 12%), lorcaserin (n = 18, 8.6%), and naltrexone slow-release/bupropion slow-release (n = 10, 4.8%). Of patients, 37% lost>5% of their total weight 1 year after pharmacotherapy was prescribed. There were significant differences in weight loss at 1 year in gastric banding versus sleeve gastrectomy patients (4.6% versus .3%, P = .02) and Roux-en-Y gastric bypass versus sleeve gastrectomy patients (2.8% versus .3%, P = .01).There was a significant positive correlation between body mass index at the start of adjuvant pharmacotherapy and total weight loss at 1 year (P = .025). Conclusion: Adjuvant weight loss medications halted weight regain in patients who underwent bariatric surgery. More than one third achieved>5% weight loss with the addition of weight loss medication. The observed response was significantly better in gastric bypass and gastric banding patients compared with sleeve gastrectomy patients. Furthermore, adjuvant pharmacotherapy was more effective in patients with higher body mass index. Given the low risk of medications compared with revisional surgery, it can be a reasonable option in the appropriate patients. Further studies are necessary to determine the optimal medication and timing of adjuvant pharmacotherapy after bariatric surgery.